2010
DOI: 10.1590/s0044-59672010000400017
|View full text |Cite
|
Sign up to set email alerts
|

Optimum dietary protein requirement for Amazonian Tambaqui, Colossoma macropomum Cuvier, 1818, fed fish meal free diets

Abstract: Fish meal free diets were formulated to contain graded protein levels as 25% (diet 1), 30% (diet 2), 35% (diet 3) and 40% (diet 4). The diets were fed to tambaqui juveniles (Colossoma macropomum) (46.4 ± 6.3g) in randomly designed recirculating systems for 60 days, to determine the optimum protein requirement for the fish. The final weight of the fish, weight gain (28.1, 28.5, 32.2, 28.0g) and specific growth rate increased (P>0.05) consistently with increasing dietary protein up to treatment with 35% protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 23 publications
6
23
1
3
Order By: Relevance
“…; Oishi et al . ). High‐lipid deposition in low protein diets can be explained by the over consumption of non‐protein nutrient such as carbohydrate and also suggested that experimental fish was able to utilize dietary carbohydrate (Arzel et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Oishi et al . ). High‐lipid deposition in low protein diets can be explained by the over consumption of non‐protein nutrient such as carbohydrate and also suggested that experimental fish was able to utilize dietary carbohydrate (Arzel et al .…”
Section: Discussionmentioning
confidence: 97%
“…Diets were based on formulations specifically developed for matrinxãs (Izel et al 2004) and tambaquis (Oishi et al 2010). The three feeds for each species contained similar nitrogen and energy levels, but each one contained a different proportion of sacha inchi (0, 15 and 30%) ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Protein efficiency ratio in this study is quite good compared to research Oishi (2010), which uses 35% protein feed to produce protein efficiency ratio amounted to 1.87 ±0.20. The lower the protein efficiency ratio protein are used to produce the body weight, the better.…”
Section: Resultsmentioning
confidence: 62%